PENGARUH SEKTOR PARIWISATA TERHADAP PENYERAPAN TENAGA KERJA DI PROVINSI JAWA TIMUR TAHUN 2012-2018 - Fathya Rizki Indah; Ida Nuraini; Yunan Syaifullah (Program Studi Ekonomi Pembangunan, 2021)
This aims of this reseach to analyze the effect of sector of tourism on absorption of labor in East Java Province in 2012-2018 (Study case: Regency/City in East Java Province). This research used secondary and the data obtained from the Tourism Office of East Java Province, the Office of Manpower and Transmigration of East Java Province and the Central Statistics Agency of East Java Province. The analysis technique in this research is panel data analysis wich is prossed using Random Effect Model (REM) . The dependent variable in this study is labor in the tourism sector in the Regency/City East Java Province in 2012-2018, while independent variables is the number of hotels, the number of restaurants, the number of tourism objects and number of tourists in the Regency / City of East Java Province in 2012. -2018. In this reseach, it is found that the variables number of hotels, the number of restaurants, the number of Tourism objects a positive and significantly. However, for the variable number of tourists a positive but does not effect absorption of labor in the tourism sector in the Regency / City of East Java Province.